Perkembangan Kompetensi Absolut Praperadilan Tentang Perintah Penetapan Tersangka Kepada Penegak Hukum oleh Pengadilan. (Studi Putusan Pengadilan Negeri Jakarta Selatan No. 24/Pid/Pra/2018/PN.Jkt.Sel) - Muhammad Tabrani Mutalib (Khairun Law Journal, 2018)
Pretrial has the authority under the Criminal Procedure Code to order law enforcement agencies (KPK / Police / Prosecutors) to continue the legal process of someone suspected of committing a criminal act of corruption and this does not conflict with the legality principle of criminal procedure as affirmed in Article 2 and Article 3 of the Criminal Procedure Code. The pretrial judge's action is the application of the principle of judicial independence to resolve legal issues. Thus the pretrial judge's ruling does not conflict with the legal principles of procedural law in Article 2 and Article 3 of the Criminal Procedure Code